Analisis Stabilitas Lereng Bendungan Terhadap Beban Gempa sebagai Upaya Pengurangan Bencana (Studi Kasus: Bendungan Jlantah) - Nurul Chayati; Muhammad Hasan Wicaksono; Fadhila Muhammad Libasut Taqwa (Universitas Batanghari Jambi, 2023)
Indonesia is a country that has quite high seismic activity and is prone to earthquake hazards, so the construction of embankment dams in Indonesia needs to pay attention to stability against collapse due to soil mass and earthquake loads. Jlantah dam is located in Karanganyar, Central Java. This dam is planned for irrigation needs of 1493 hectares and raw water of 150 liters/second. This study aims to determine the safety factor (Fs) on the Jlantah Dam body. The method used is a quantitative data analysis method, the calculation of the earthquake coefficient corrected by OBE and MDE, carried out with the help of a computer program, namely GeoStudio 2012. Meanwhile, if the earthquake coefficient is known not to be Fs 1.5. The method used is based on references from KP 02-Planning Criteria for Main Building Section and KP 06-Planning Criteria for Parameters Section, and Pd T-14-2004-A. The terms (Fs 1,2) which are used as the theoretical basis are quoted from the theory of Prof. Hoek (1981) stated that by knowing the earthquake coefficient, Fs 1.2 can be used, while if the earthquake coefficient is not known Fs 1.5 Analysis of Earthquake Backfill Type Dam Stability. From the results of the study, it was found that at the time of maximum water and the earthquake for the road dam body was declared from a good structural failure. The results of the bottom study on MDE earthquake conditions from the maximum water level obtained Fk > 1.0 Fk minimum, the maximum water level obtained Fk > 1, 2 Fk minimum with OBE earthquake conditions.